An Appraisal Among Wired, Hybrid and Wireless Smart Homes to Mitigate Electromagnetic Radiation - Raveendran, Reshna; Tabet Aoul, Kheira Anissa (Frontiers in Built Environment, 2022)
The global Covid-19 pandemic caused a rapid transitioning to remote work settings, one likely to linger post-pandemic, resulting on people spending more time at home for work or study. The globalpandemic defined a new normal that is expected to be digital and heavily relying on technology. Smart buildings which are envisioned to be the next paradigm shift in the built environment are also foreseen as a response solution to aid in situations like pandemic. However, such a move yields benefits as well as risks, prompting wide debates on the priority to safeguard building occupants health, safety and well-being. Researchers, designers and engineers are seeking solutions to incorporate or modify design features in the indoor environment that prioritize the dwellers’ health and wellness. Though benefits of smart and IoT devices aid in monitoring health and wellness, radiation from these wireless devices may cause harm to human health, especially those with weaker health, as indicated by several research findings. Some of the negative impacts from wireless radiation include cell damage, cancer, tumor, change in hormonal levels, and neurological damage. Thus, this study seeks to determine the difference in radiation level inside a wired, hybrid and a wireless smart home through Computer Simulation Technology (CST) simulation. Such a quantification can help designers develop strategies to design smart buildings that cause low radiation for its occupants. Antenna field source was imported to CST to create the wireless and hybrid design scenario. The measurement for wired and hybrid were evaluated keeping the wired design as baseline. The results revealed that wireless produced 26.55% more radiation than wired scenario at 2.45 GHz, taken as baseline measurement. Further, the total Electromagnetic Radiation (EMR) and radiation patterns are dependent on several factors like proximity of IoT and smart devices to building walls and interior furnishings, frequency of operation. In order to create a safer indoor environment, this study recommends the use of both wired and hybrid design in lieu of totally wireless smart buildings.